รูปแบบการวิเคราะห์องค์ประกอบต้นทุนในการจ้างเหมางานบำรุงปกติทางหลวง - ฟ้าใหม่ แก้วรัตนปัทมา (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objective of this research is to develop a framework to analyze cost components and factors determining cost-effectiveness of contracting out routine road maintenance. Cases from Department of Highways (DOH) of Thailand were used as a basis for the study. The research comprised two major tasks. First, related cost components were investigated to understand changes on costs resulting from outsourcing routine maintenance works both in short and long terms, and to identify cost-influenced factors. This task involved document reviews and analyzes of DOH data. The results were then verified with DOH experts regarding practicality of such results. The second task involved analysis of case studies which were taken from actual cost data of DOH. The purpose of analysis was to identify data and assumptions required in the calculation as well as to study impacts from each type of cost-influenced factors. Skin patching, deep patching, and grass cutting are maintenance activities which were used in this analysis. In case of contracting out, there are three cost components that should be considered: 1) in-house operating costs which cannot be reduced, 2) private contract cost, 3) contract procurement, administration, and inspection costs. In the past, government agencies have maintained resources to carry out most of the works in-house. The reduction of operating costs would significantly impact cost-effectiveness of outsourcing decision. The direct costs that may not be fully reduced are direct personnel costs, and machine and vehicle costs. In the short run, these costs can be decreased if they can be utilized elsewhere. In the long run, direct personnel costs can be gradually reduced, while the reduction of machine and vehicle costs has to concern with the capabilities of the agencies to response on emergency situation. As for indirect costs, contracting out a small amount of maintenance works may not cause significant impacts to supporting personnel costs as well as other indirect costs. The analysis of case studies reveals varied impacts caused by different factors resulting from dissimilar cost structure of each maintenance activities. It reflects diverse cost-effectiveness potential from outsourcing decision.